(3ebOeI GdhGLHs - (3GdNhGfSGQj, GdNhGfSGQj, MSjf Hf eMeO Hf GdMSjf GdNhGfSGQj, J (B1131(3g`s ((3MSjf Hf MGL Ydj GdNSQhTGgjs)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg GdPj LYd GeJKGd ChGeQg SHHG dGbJHGS GdKhGH hUjQ GdGfJgGA Yf fhGgjg TQWG ddNdGU (B... (3Ef GdhGLH Ydi bSejf eWdb heTQhW hYnqQahG GdeWdb HeG de jbjO hLhHgs
(3BNQgG (B:s
(3BNQgG(B: (3hgPG HfGA Ydi hLhH GdebOeI ceG dG jNai hcPG hUa GdeTJHgI HGdCLfHjI HGdJMQje hcPG fPQ haYd hGLH Ch JYdjbg Ydjg Ch JYdjb GdXgGQ Ydjg hcPG GdhUa HGdaSb HYO JQc GdebOeI bHd ONhd ReGf JQc GdhGLHs
(3JHUQI GdeDda (B:s
(3CQN haGJg UGMH eYLe GdeDdajf SfI (B1099(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf, L (B1: 636s
(3GdPQjYI, L (B22: 67s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3CUhd Gdabgs